The biological standard of living in urban Bolivia, 1880s-1920s: Stagnation and persistent inequality - Boris Sergio Branisa Caballero; José Peres-Cajías; Nigel Caspa (Institute for Advanced Development Studies (INESAD), 2019)
Based on almost 5.000 direct observations on National Identification Cards, this paper offers the first estimation of the evolution of average heights in urban Bolivia for the decades 1880s-1920s. The analysis focuses on men aged 19-50 years registered in the city of La Paz. Despite city's growing economic importance and modernization, average heights remained stagnant around 163 cm. This level is not so different to that found in the still disperse available evidence for rural Bolivia. Furthermore, there is evidence of inequalities throughout the period under study: those men who were indigenous, illiterate or worked in manual occupations were persistently shorter than non-indigenous, literates and non-manual workers, respectively. In coincidence with recent studies on Latin America, these findings suggest that the boost in exports and the regained dynamism of the economy that took place at the onset of the 20th century were not accompanied by improvements in biological standards of living.
Keywords: I31; N16; N36; 330; anthropometric history; heights; welfare; inequality; first globalization